Osteochondrosis dissecans of the shoulder glenoid fossa diagnosed in four throwing athletes - Rossi, F.; Dragoni, S. (The Journal of Sports Medicine and Physical Fitness, 2006)
The aim of this study was to report 4 observations of osteochondrosis dissecans (OCD) of the shoulder glenoid fossa diagnosed in throwing athletes. A retrospective review of medical and radiological records of throwing athletes, performed for the period 1992 to 2002, revealed 215 studies of the shoulder. The patients were elite throwing athletes suffering for recurrent shoulder pain. Four cases (1.86%) of OCD of the glenoid fossa were identified; conventional radiographs of the shoulder were taken for all patients followed by MR examination. All cases received a definitive surgical diagnosis.